Influence of Sunlight Incidence and Fruit Chemical Features on Oviposition Site Selection in Mango by Anastrepha obliqua: Implications for Management - Larissa Guillén; Juan L. Monribot-Villanueva; José A. Guerrero-Analco; Rafael Ortega; Alma Altúzar-Molina; Victoria Mena; Eliel Ruiz-May; Martín Aluja (Insects, 2022)
With the aim of identifying key factors that determine oviposition decisions by Anastrepha obliqua for management purposes, we conducted a behavioral study under natural/semi-natural field conditions to identify where exactly in the fruit (upper, middle, or lower sections) females preferred to lay eggs in a highly susceptible mango cultivar (“Criollo”), and whether sunlight incidence and fruit chemical compounds influenced oviposition site selection by this pestiferous fly. Females oviposited in shaded, upper fruit sections where pulp had higher total carbohydrate concentrations but similar total protein, lipid, and polyphenol concentrations than non-oviposited sections. Peel had higher overall nutrient and mangiferin/quercetin-3-D-galactoside (polyphenols) concentrations. An untargeted metabolomic analysis of oviposited and non-oviposited fruit sections identified abscisic acid (ABA) and dihydrophaseic acid glucoside, a by-product of ABA catabolism, as potential chemical markers that could play a role in fruit acceptance behaviors by female flies. We conclude that females preferentially oviposit in fruit sections with optimal chemical and environmental conditions for larval development: more carbohydrates and antioxidants such as mangiferin and ferulic acid and lesser sunlight exposure to avoid lethal egg/larval desiccation/overheating. We make specific recommendations for A. obliqua management based on female host selection behavior, a tree pruning scheme exposing fruit to direct sunlight, application of a host marking pheromone, and the use of egg sinks in the orchard.